2015
DOI: 10.5455/aim.2015.23.206-209
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Production of Medical Universities in the West of Iran: a Scientometric Analysis

Abstract: Introduction:This study aimed to compare scientific production by providing quantitative evaluation of science output in five Western Iranian Medical Universities including Hamedan, Ilam, Kermanshah, Kurdistan and Lorestan University of Medical Sciences using scientometrics indicators based on data indexed in Scopus for period between the years 2010 to 2014.Methods:In this scientometric study data were collected using Scopus database. Both searching and analyzing features of Scopus were used to data retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Moreover, these universities have the highest share of staff with higher academic positions. Results of a study by Rasoulabadi et al (2015) also indicated that the trend of scientific publications in Iranian medical universities although increasing, has not been stable [14]. Research policies in Iran might be developed in an equitable way to encourage and promote scientific production in small universities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these universities have the highest share of staff with higher academic positions. Results of a study by Rasoulabadi et al (2015) also indicated that the trend of scientific publications in Iranian medical universities although increasing, has not been stable [14]. Research policies in Iran might be developed in an equitable way to encourage and promote scientific production in small universities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it should not be ignored that part of the Iranian research materials, and also other countries with non-English language, are not covered by indexing databases due to the so called language bias [14,26]. The vast majority of international databases that evaluate scientific products only or adequately archive English articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROP is a major cause of blindness in infants and in many cases is predictable and curable ( 13 ). Regarding the significant increase in the survival rate of premature infants and high prevalence of ROP in the Eastern Mediterranean area and the need for more information on risk factors, this study was conducted to determine the prevalence of retinopathy of prematurity and its related factors in Sanandaj, Iran ( 14 ). In this study, the prevalence of ROP in infants was 10.6%.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that all patients who referred to the dentistry faculty of Babol University of Medical Science, Babol, Iran, were examined and included in the study if they satisfied the inclusion criteria of the study (Rasolabadi et al, 2015). Inclusion criteria were as follows; age above 18 years, having more than 20 healthy teeth, having at least an area with the pocket depth of 4 mm or more in at least two quadrants of the mouth with bleeding on gentle probing, and the patient who had a plaque index value less than 30 percent (before measuring the desired variables, the patients were unified in terms of the bacterial plaque index).…”
Section: The Participants and Requirementsmentioning
confidence: 99%